PENGARUH MODEL COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN BERPIKIR LOGIS PADA ANAK USIA 5-6 TAHUN DI TK AN NUR JAMBI KECIL KABUPATEN MUARO JAMBI - Nilam Cahya; Indriyani; Rizki Surya Amanda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The limited use of media and teaching aids in the learning process has resulted in less effective delivery of material. Consequently, children’s learning activities have not been fully optimized, leading to inadequate development in understanding number concepts and logical thinking skills. One potential solution is the application of the Teams Games Tournament (TGT) method, a cooperative learning model that incorporates elements of competition within a game format while emphasizing collaboration among group members. This study aims to examine the effect of the Cooperative Learning model, specifically the TGT type, on improving logical thinking skills through group-based smart board games in children aged 5–6 years at TK An-Nur Jambi Kecil, Muaro Jambi. A quantitative research approach was employed using an experimental design, namely the Pretest-Posttest Control Group Design. The research population consisted of all 29 students of TK An-Nur Jambi Kecil. Sampling was conducted using a total sampling technique, with Class A (14 students) serving as the control group and Class B (15 students) as the experimental group that received the TGT learning treatment. The research instrument used was an observation sheet developed based on indicators of logical thinking skills in early childhood. Data were analyzed descriptively to compare logical thinking abilities before and after the treatment. Furthermore, statistical analysis included the Shapiro-Wilk normality test, Independent Sample T-Test for homogeneity, and Paired Sample T-Test for hypothesis testing. The findings revealed that the implementation of the Cooperative Learning TGT model had a significant effect on children’s logical thinking skills at the age of 5–6 years in TK An-Nur Jambi Kecil. This conclusion is supported by the increase in average posttest scores compared to pretest scores and statistical test results showing that the calculated t value exceeded the table value, with a significance level of < 0.05. Therefore, the TGT model is proven effective in enhancing logical thinking skills in early childhood education.